Islam dan Sekularisme dalam Al-Qur’an - Adhelia Ananta; Aisyah Safitri; Charitsatun Najah; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
Secularism is seen as a teaching that does not have a strong foundation in Islam, both in concept and in action. In the next stage, secularism grew more complex to the point that it became a debate among Muslims. Therefore, insights about secularism, both its background and its essence, should be understood, especially by Muslims. This study uses a qualitative method with more emphasis on descriptive writing and interpreting the verses using the Maudu'i method. The word secularism was first mentioned by George Jacob Holyoake. In its historical development, secularism manifested itself regarding the need to break worldly life to solve religious problems. In the Qur'an, there are verses on secularism, some of which are Q.S. al-Baqarah: 85–86, Q.S. Hud: 15–16, and Q.S. al-Isra: 18.